2017
DOI: 10.1108/ijlm-04-2015-0071
|View full text |Cite
|
Sign up to set email alerts
|

Towards more efficient logistics: increasing load factor in a shipper’s road transport

Abstract: Purpose Increasing load factor is crucial for transport efficiency and may benefit shippers because of its potential to reduce both environmental impact and transportation costs. The purpose of this paper is to explore how shippers can increase load factor in their road transport by identifying opportunities for logistics action and influences on load factor performance measures created by such opportunities. Design/methodology/approach A case study is performed of the outgoing goods flow from the central wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The major contributions of the current study are two-fold. First, the study looks at the load factor issue from the perspectives of shippers to overcome the limitations of earlier studies, as suggested, for example, by Santén (2017). In other words, in addition to the carriers' opinions, the shippers' perspectives should be considered when judging the appropriateness of freight policies for increasing loads on trucks.…”
Section: Discussionmentioning
confidence: 99%
“…The major contributions of the current study are two-fold. First, the study looks at the load factor issue from the perspectives of shippers to overcome the limitations of earlier studies, as suggested, for example, by Santén (2017). In other words, in addition to the carriers' opinions, the shippers' perspectives should be considered when judging the appropriateness of freight policies for increasing loads on trucks.…”
Section: Discussionmentioning
confidence: 99%
“…Logically, other considerations can be of greater relevance in the selection (for example, commercial or strength considerations), which would make the other box types more interesting even though they are more inefficient. The larger the boxes are in terms of useful volume (for one type), the smaller the relative consumption of cardboard (and waste) per m 3 (Figure 3). This is a critical aspect of the proposed model, given that its ultimate aim is to seek solutions that improve the m 2 /m 3 ratio among the feasible solutions on the graph (ideally, the optimum one).…”
Section: Slotted Box Folder Box Telescope Boxmentioning
confidence: 99%
“…The larger the boxes are in terms of useful volume (for one type), the smaller the relative consumption of cardboard (and waste) per m 3 (Figure 3). This is a critical aspect of the proposed model, given that its ultimate aim is to seek solutions that improve the m 2 /m 3 ratio among the feasible solutions on the graph (ideally, the optimum one).…”
Section: Slotted Box Folder Box Telescope Boxmentioning
confidence: 99%
See 1 more Smart Citation
“…The demonstration of the assessment framework is performed based on the opinion of the Supply chain stakeholder category and data for two lifecycle stages, creation-construction and operation. The lifecycle stages of the measure are [44,45]:…”
Section: Application Of Frameworkmentioning
confidence: 99%